On the Possibility of Using Medical Linear Electron Accelerators as a Source of the Reference Pulsed Photon Radiation Field - A. A. Zaharadniuk; A. Y. Taraev; S. V. Lazarenko (Приборы и методы измерений, 2023)
Sources of pulsed photon radiation are widely used in science and industry. In this regard, there is a growing demand for dosimetry instruments capable of operating in these pulsed photon radiation fields. Until now there is no comprehensive methodology that describes the characteristics of reference fields of pulsed photon radiation required for calibration and verification of dosimetry equipment. The aim of this paper was to study the possibility of using a medical linear electron accelerator as a generating source of a reference pulsed photon radiation field. The paper investigates main characteristics of photon radiation field (namely, spectrum and average energy) generated by CLINAC in two modes of operation: 6 MV and 18 MV. Additionally it researches the possibility of attenuation of the CLINAC photon radiation intensity by a lead filter. The spectrum and average energy of the CLINAC photon radiation were calculated by means of Monte Carlo simulation in the Fluka program. The validation of the calculation was determined by comparing the attenuation coefficients calculated by the model with ones obtained experimentally by using real CLINACs. Experimentally, the attenuation coefficients were obtained by measuring the air kerma rate generated by the photon radiation fields of Varian VitalBeam and Varian iX CLINACs at a given point of space. Based on the simulation results, the Ḣ*(10) ambient dose equivalent ratio generated by CLINACs were calculated. It was found that the lead filter effectively attenuates the CLINAC photon radiation in terms of both air kerma rate and ambient dose equivalent rate to levels suitable for calibration of dosimetry equipment designed to measure pulsed radiation. It is shown that the lead filter significantly affects both the photon spectrum of the CLINAC and its average energy.